2018
DOI: 10.5223/pghn.2018.21.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation to Patients with Refractory Very Early Onset Ulcerative Colitis

Abstract: Recently, fecal microbiota transplantation (FMT) has been attracting attention as a possible medical treatment of ulcerative colitis (UC). A randomized controlled trial of FMT for children with UC is currently underway. Therapeutic effects of FMT for adults with UC remain controversial. We report two cases of early-onset UC in children. A patient was diagnosed with UC at age 1-year 9-month and underwent FMT at age 2-year 3-month. He attained clinical remission for three weeks after FMT, but then relapsed at fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…FMT involves the transferring of a fecal matter solution from a donor's to a recipient's intestine to alter the gut microbiota and grant a clinical benefit [ 31 ]. In a case report by Yodoshi and Hurt, a five-year-old female was treated using FMT for her diagnosed UC that had affected the entire colon at the age of two years and 10 months [ 11 ]. The patient achieved clinical remission after one week, with a pediatric ulcerative colitis activity index (PUCAI) score of 0.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FMT involves the transferring of a fecal matter solution from a donor's to a recipient's intestine to alter the gut microbiota and grant a clinical benefit [ 31 ]. In a case report by Yodoshi and Hurt, a five-year-old female was treated using FMT for her diagnosed UC that had affected the entire colon at the age of two years and 10 months [ 11 ]. The patient achieved clinical remission after one week, with a pediatric ulcerative colitis activity index (PUCAI) score of 0.…”
Section: Discussionmentioning
confidence: 99%
“…After three months, the fecal analysis demonstrated that the patient's intestinal flora was similar to the donor's fecal matter. As a result, clinical remission of UC activity was sustained for a period of two years since the study was published [ 11 ]. An adequate understanding of the mechanisms of VEO-IBD and disease advancement is needed to devise targeted therapeutic strategies for this patient population and improve their outcomes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…et al, 2016). To the best of our knowledge, the youngest reported patient that underwent FMT for very early-onset IBD was 2 years and 3 months old (Yodoshi and Hurt, 2018).…”
Section: Conveying the Present To The Future For Fighting Against Antmentioning
confidence: 99%
“…A valid alternative to cyclosporine or infliximab as rescue therapy in patients with acute severe UC is still lacking 7779. Antibodies toward interleukins (ILs)-12/23 (ustekinumab) and tofacitinib (a not biologic small molecule inhibiting Janus Kinase) have been used in small series of patients with severe UC but it is too early to hypothesize their use 80,81…”
Section: Future Directionsmentioning
confidence: 99%